On some degree based topological indices of mk-graph. (17th August 2020) - De, Nilanjan; Cancan, Murat; Alaeiyan, Mehdi; Farahani, Mohammad Reza
Abstract: A topological index is a real number which is same under graph isomorphism and it is derived from a graph by mathematically. In chemical graph theory, a molecular graph is a simple graph having no loops and multiple edges in which atoms and chemical bonds are represented by vertices and edges respectively. Topological indices defined on these chemical molecular structures can help researchers better understand the physical features, chemical reactivity, and biological activity. In this paper, we compute general expressions of some degree based topological indices of a special graph named as mk -graph for some positive integer k .